Metody obniżania kosztu ubezpieczenia w podmiotach gospodarczych - Kwiecień, Ilona (Methods of Reducing Insurance Cost in Enterprises, 2006)
The article presents the problem of insurance cost from the view of insured enterprise. The author indicates and discusses the following techniques of bringing this cost down: negotiations, individual risk reduction, prevention, risk retention and also alternative solutions usage in the organizational sphere of designing and placing insurance plan, like risk groups, mutual insurance or captives. However, these methods should be used knowingly, in the safety way, assuring right insurance cover. For that reason using of insurance should be preceded by risk analysis
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 394-402